PHILOSOPHY OF COMMUNICATION: ANALYSIS OF THE BASIC PARADIGMS - Іщук, С. М. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2015)
The best known approaches to the definition of communication are analyzed in the article. The idea of a paradigmatic multivariate approach to the philosophy of communication is grounded.